Chronic intermittent mental stress promotes atherosclerotic plaque vulnerability, myocardial infarction and sudden death in mice. Issue 1 (September 2015) - Roth, Lynn; Rombouts, Miche; Schrijvers, Dorien M.; Lemmens, Katrien; De Keulenaer, Gilles W.; Martinet, Wim; De Meyer, Guido R.Y.
Abstract: Vulnerable atherosclerotic plaques are prone to plaque rupture leading to acute cardiovascular syndromes and death. Elucidating the risk of plaque rupture is important to define better therapeutic or preventive strategies. In the present study, we investigated the effect of chronic intermittent mental stress on atherosclerotic plaque stability and cardiovascular mortality in apolipoprotein E-deficient (ApoE −/− ) mice with a heterozygous mutation in the fibrillin-1 gene (Fbn1 C1039G+/ − ). This mouse model displays exacerbated atherosclerosis with spontaneous plaque ruptures, myocardial infarction and sudden death, when fed a Western-type diet (WD). Female ApoE −/− Fbn1 C1039G+/− mice were fed a WD for up to 25 weeks. After 10 weeks WD, mice were divided in a control (n = 27) and mental stress (n = 29) group. The chronic intermittent mental stress protocol consisted of 3 triggers: water avoidance, damp bedding and restraint stress, in a randomly assigned order lasting 6 h every weekday for 15 weeks. Chronic intermittent mental stress resulted in a significant increase in the amount of macrophages in atherosclerotic plaques of the proximal ascending aorta, whereas type I collagen and fibrous cap thickness were decreased. The coronary arteries of mental stress-treated mice showed larger plaques, more stenosis, and an increased degree of perivascular fibrosis. Moreover, myocardial infarctions occurred more frequently in the mental stress group. As compared to the control group, the survival of stressed ApoE −/− Fbn1 C1039G+/− mice decreased from 67% to 52% at 25 weeks WD, presumably due to myocardial infarctions. In conclusion, chronic intermittent mental stress promotes plaque instability, myocardial infarctions, and mortality of ApoE −/− Fbn1 C1039G+/− mice. Highlights: Mental stress enhanced plaque vulnerability in ApoE −/− Fbn1 C1039G+/− mice. Coronary plaques were larger and more stenotic after mental stress treatment. Perivascular fibrosis of coronary arteries was increased. The occurrence of myocardial infarctions was higher as a result of stress. Survival in stressed ApoE −/− Fbn1 C1039G+/− mice was decreased.